The Karyopherin proteins, Crm1 and Karyopherin β1, are overexpressed in cervical cancer and are critical for cancer cell survival and proliferation - van der Watt, Pauline J. (Int J Cancer, 2009)
The Karyopherin proteins are involved in nucleo-cytoplasmic trafficking and are critical for protein and RNA subcellular localization. Recent studies suggest they are important in nuclear envelope component assembly, mitosis and replication. Since these are all critical cellular functions, alterations in the expression of the Karyopherins may have an impact on the biology of cancer cells. In this study, we examined the expression of the Karyopherins, Crm1, Karyopherin β1 (Kpnβ1) and Karyopherin α2 (Kpnα2), in cervical tissue and cell lines. The functional significance of these proteins to cancer cells was investigated using individual siRNAs to inhibit their expression. Microarrays, quantitative RT-PCR and immunofluorescence revealed significantly higher expression of Crm1, Kpnβ1 and Kpnα2 in cervical cancer compared to normal tissue. Expression levels were similarly elevated in cervical cancer cell lines compared to normal cells, and in transformed epithelial and fibroblast cells. Inhibition of Crm1 and Kpnβ1 in cancer cells significantly reduced cell proliferation, while Kpnα2 inhibition had no effect. Noncancer cells were unaffected by the inhibition of Crm1 and Kpnβ1. The reduction in proliferation of cancer cells was associated with an increase in a subG1 population by cell cycle analysis and Caspase-3/7 assays revealed increased apoptosis. Crm1 and Kpnβ1 siRNA-induced apoptosis was accompanied by an increase in the levels of growth inhibitory proteins, p53, p27, p21 and p18. Our results demonstrate that Crm1, Kpnβ1 and Kpnα2 are overexpressed in cervical cancer and that inhibiting the expression of Crm1 and Kpnβ1, not Kpnα2, induces cancer cell death, making Crm1 and Kpnβ1 promising candidates as both biomarkers and potential anticancer therapeutic targets.